Avaliação de Programas de Alimentação para Matrizes de Corte na Fase de Produção - Argenta, João Artur; Sakomura, Nilva Kazue [UNESP]; De Azevedo Jr., Pedro Cláudio (My University, 2001)
The experiment was conducted to evaluate the best feeding program post peak egg production for broiler breeders. Cobb broiler breeders (3168 females and 352 males) were distributed in a randomized experimental design with four treatments and eight replicates per treatment, with 99 females and 11 males per replicate. The evaluated programs were: Program 1 - Reduction 1 g of feed/bird/day/week for each drop of 0.5 points of the egg mass. Program 2 - Reduction of 1 g of feed/bird/day/week post peak production until the end of production period, regardless the percentage of the egg production. Program 3 - Reduction of 3 g of feed/bird/day/week, in the first week post peak production, 2 g of feed/bird/day/week in the second week and 1 g of feed/bird/day/week on the following weeks. Program 4 - Reduction of 5 g of feed/bird/day/week, in the first week post peak production, 3 g of feed/bird/day/week in the second week and 1 g of feed/bird/day/week on the following weeks. According to the results of feed intake per egg, the best program was the program 1, followed by programs 3, 2 and 4. It was recommended the program 1 for Cobb broiler breeders with peak egg production in the winter.
Evaluation of Feeding Programs for Broiler Breeders Hens
Keywords: Broiler breeders; Feeding programs; Reproduction period